The Oregon Trail. Beginnings [videorecording (VHS)] - Boettcher, Steven J.; Trinklein, Michael J. (Films for the Humanities & Sciences [distributor], 1993)
Relates the events that led to the opening of the Oregon Trail and explains its role in American history. Includes the following topics: Lewis and Clark and the Astorians; the first emigrants and the Great Migration; the reasons why so many went West; and the beginnings and preparations for a typical journey.